Pengaruh Whistleblowing, Ketaatan Aturan Akuntansi, Dan Komitmen Organisasi Terhadap Kecenderungan Kecurangan (Fraud) Akuntansi Pada LPD Se- Kecamatan Penebel - Ni Kadek Kristina Devi; I Wayan Sudiana (Hita Akuntansi dan Keuangan, 2023)
Fraud is a form of violation where accounting practices are not carried out in accordance with the applicable rules in an institution. Fraud certainly needs to be prevented so as not to have a bad impact on the company. This research was conducted to analyze the factors that can cause fraud in the organization such as whistleblowing, compliance with accounting rules and organizational commitment. LPD employees throughout Penebel District are used as a population with a research sample of 163 people whose data will be analyzed using multiple linear regression analysis techniques. The results show that tax whistleblowing, compliance with accounting rules, and organizational commitment have a reverse or negative relationship with the tendency of accounting fraud.